2015
DOI: 10.1186/s12914-015-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of human papillomavirus and factors associated with intention to obtain HPV vaccination among Korean youth: quasi experimental study

Abstract: BackgroundThis study aimed to determine the awareness among fifth-grade girls and boys of sexually transmitted diseases (STDs), cancer, and human papillomavirus (HPV), and to determine the factors associated with intention to obtain the HPV vaccination.MethodsA quasi experimental design was employed with Korean fifth-grade students as the subjects for this study (n=117). Prior to providing HPV education, the awareness and health beliefs regarding STDs and cancer prevention were assessed according to gender. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Increased number of STI incidence could be explained by two ways: the number of healthcare centers that reports have increased or the current social trend for increasing number of sexual activity and lowering of sexual activity initiation age. Adolescents who did not get STI treatment were 44.7% [4]. In previous study, among adolescents, homeless adolescent has very high prevalence of STIs [23].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Increased number of STI incidence could be explained by two ways: the number of healthcare centers that reports have increased or the current social trend for increasing number of sexual activity and lowering of sexual activity initiation age. Adolescents who did not get STI treatment were 44.7% [4]. In previous study, among adolescents, homeless adolescent has very high prevalence of STIs [23].…”
Section: Discussionmentioning
confidence: 87%
“…Also, each school's health center, where most of adolescent can easily access to, should be equipped simple STI test tool. Also, as previous studies [4,14,15] suggested, it might be beneficial to rearrange and intensify formal STI surveillance.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations